Shadow force [videorecording (DVD)] - Carnahan, Joe; Chills, Leon; Washington, Kerry, 1977-; Sy, Omar, 1978-; Strong, Mark, 1963-; Randolph, Da'Vine Joy, 1986-; Method Man; Kamara, Jahleel; Azpiroz, Juanmi; Hasbourne, Tiffany; DeLeon, Craig (Lionsgate, 2025)
"In Shadow Force, Kyrah and Issac were once the leaders of a multinational special forces group called Shadow Force. They broke the rules by falling in love, and in order to protect their son, they go underground. With a large bounty on their heads, and the vengeful Shadow Force hot on their trail, one family's fight becomes and all-out war."--